The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/gcb.15252
|View full text |Cite
|
Sign up to set email alerts
|

Additive impacts of deoxygenation and acidification threaten marine biota

Abstract: Deoxygenation in coastal and open‐ocean ecosystems rarely exists in isolation but occurs concomitantly with acidification. Here, we first combine meta‐data of experimental assessments from across the globe to investigate the potential interactive impacts of deoxygenation and acidification on a broad range of marine taxa. We then characterize the differing degrees of deoxygenation and acidification tested in our dataset using a ratio between the partial pressure of oxygen and carbon dioxide (pO2/pCO2) to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Our meta-analysis revealed a prevalence of additive interactions between OA and heavy metals, indicating that cumulative effects of OA and heavy metals on marine biota can be reasonably well assessed by summing the single stressor impacts. The prevalence of additive interactions discovered in the present study agrees well with previous meta-analysis studies, in which most stressor interactions were additive across experimental studies (Darling and Côté, 2008;Przeslawski et al, 2015;Jin et al, 2019;Steckbauer et al, 2020), while overall synergisms or antagonisms were uncommon (Burkepile and Hay, 2006;Stephens et al, 2013;Jackson et al, 2016;Yue et al, 2017). Because OA had positive effects on organisms and most frequently interacted additively with heavy metals, our analysis found that OA alleviated the harmful effects of heavy metals, leading to an overall neutral effect co-exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Our meta-analysis revealed a prevalence of additive interactions between OA and heavy metals, indicating that cumulative effects of OA and heavy metals on marine biota can be reasonably well assessed by summing the single stressor impacts. The prevalence of additive interactions discovered in the present study agrees well with previous meta-analysis studies, in which most stressor interactions were additive across experimental studies (Darling and Côté, 2008;Przeslawski et al, 2015;Jin et al, 2019;Steckbauer et al, 2020), while overall synergisms or antagonisms were uncommon (Burkepile and Hay, 2006;Stephens et al, 2013;Jackson et al, 2016;Yue et al, 2017). Because OA had positive effects on organisms and most frequently interacted additively with heavy metals, our analysis found that OA alleviated the harmful effects of heavy metals, leading to an overall neutral effect co-exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Another meta‐analysis showed that hydrogen sulphide (H 2 S) also reduces the survival time of marine organisms under hypoxia by an average of 30% (Vaquer‐Sunyer & Duarte, 2010). Acidification was shown to have additive or synergistic negative effects combined with hypoxia (Gobler & Baumann, 2016; Steckbauer et al, 2020). Since all these factors usually co‐occur during hypoxic events, in situ sponge thresholds to hypoxia could be lower than determined through single stressor laboratory experiments (Diaz & Rosenberg, 1995; Steckbauer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Acidification was shown to have additive or synergistic negative effects combined with hypoxia (Gobler & Baumann, 2016; Steckbauer et al, 2020). Since all these factors usually co‐occur during hypoxic events, in situ sponge thresholds to hypoxia could be lower than determined through single stressor laboratory experiments (Diaz & Rosenberg, 1995; Steckbauer et al, 2020). Future experiments that evaluate the combined effect of these factors will be crucial to understand the full response of sponges to hypoxia in natural ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recently reported time-series data suggest the occurrence of upwelling-induced continuous hypoxia events (~1–2 weeks) in shallower layers 37 . In our study, however, natural phytoplankton assemblages and the diatom T. weissflogii benefited from reduced O 2 concentrations that were low enough to be detrimental for most marine animals 15 , 38 . Accordingly, even under elevated CO 2 conditions, low O 2 -enhanced photosynthesis can accelerate “re-oxygenation” in illuminated waters by ~193–250% (based on the net photosynthetic values of day 5 in Fig.…”
Section: Discussionmentioning
confidence: 49%